Peningkatan Imunitas dengan Konsumsi Vitamin C dan Gizi Seimbang Bagi Ibu Hamil Untuk Cegah Corona Di Kota Tegal - Hidayah, Seventina Nurul; Izah, Nilatul; Andari, Istiqomah Dwi (Universitas Nusantara PGRI Kediri, 2020)
Corona or Covid-19 virus is increasingly prevalent in a number of countries, now everyone is required to start increasing stamina, including pregnant women. Those who are pregnant certainly have to ensure that their nutritional intake can be met so that the body's immune system remains stable, so that dangerous viruses do not easily attack. In an effort to increase immunity in the midst of the Covid-19 pandemic, taking vitamin C is one of the recommended ways and also an increase in food nutrition. This community service activity was carried out to improve the quality of balanced nutrition intake of pregnant women by providing food assistance and increasing immunity by consuming vitamin C during the Covid-19 Pandemic in Margadana Village, Tegal City. The result of this community service is the distribution of basic food and Vitamin C assistance, especially for pregnant women in the Margadana District of Tegal City during the Covid Pandemic period 19.